Preparation and Characterization of Cellulose-clay Composite using Indonesian Natural Bentonite for Cr(VI) Adsorption - Julinawati, Julinawati; Nadia, Eka; Mustafa, Irfan; Suryati, Suryati (Pandawa Institute, 2025)
Contamination of Cr(VI) is of global concern, whereas the innovation in wastewater treatment is required. Combination of bentonite and cellulose could produce an effective adsorbent to treat Cr(VI)-containing wastewater. The aim of this study was to investigate the use of composite bentonite/cellulose (B/Cell) to remove Cr(VI) in the aqueous media, in which the bentonite was collected from local sources. The Na-bentonite was firstly prepared before proceeding to cellulose embedment. The resultant B/Cell was characterized for its functional groups, morphology, and crystallinity. The Cr(VI) adsorption capacity and removal efficiency were determined based on batch adsorption. Our findings revealed that the B/Cell composite with a 4:1 bentonite-to-cellulose mass ratio exhibited the highest removal efficiency (85.68%) among tested formulations. Fourier-transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction analyses confirmed the successful integration of cellulose and structural modification of bentonite. Optimal adsorption was achieved at pH 3, 180-min contact time, and 10 g/L adsorbent dosage. Isotherm modeling showed excellent fits for Sips (R2 = 0.9992) model, with maximum adsorption capacity reaching 192.56 mg/g. Kinetic analysis indicated pseudo-second-order kinetics (R2 = 0.959, qe = 1.018 mg/g), suggesting a chemisorption mechanism. These results highlight the potential of the B/Cell composite as an efficient and low-cost adsorbent for Cr(VI) removal from aqueous environments.